Higher Risk of Ischemic Events in Secondary Prevention for Patients With Persistent Than Those With Paroxysmal Atrial Fibrillation. Issue 10 (October 2016) - Koga, Masatoshi; Yoshimura, Sohei; Hasegawa, Yasuhiro; Shibuya, Satoshi; Ito, Yasuhiro; Matsuoka, Hideki; Takamatsu, Kazuhiro; Nishiyama, Kazutoshi; Todo, Kenichi; Kimura, Kazumi; Furui, Eisuke; Terasaki, Tadashi; et al.
Abstract : Background and Purpose—: The discrimination between paroxysmal and sustained (persistent or permanent) atrial fibrillation (AF) has not been considered in the approach to secondary stroke prevention. We aimed to assess the differences in clinical outcomes between mostly anticoagulated patients with sustained and paroxysmal AF who had previous ischemic stroke or transient ischemic attack. Methods—: Using data from 1192 nonvalvular AF patients with acute ischemic stroke or transient ischemic attack who were registered in the SAMURAI-NVAF study (Stroke Management With Urgent Risk-Factor Assessment and Improvement-Nonvalvular AF; a prospective, multicenter, observational study), we divided patients into those with paroxysmal AF and those with sustained AF. We compared clinical outcomes between the 2 groups. Results—: The median follow-up period was 1.8 (interquartile range, 0.93–2.0) years. Of the 1192 patients, 758 (336 women; 77.9±9.9 years old) and 434 (191 women; 77.3±10.0 years old) were assigned to the sustained AF group and paroxysmal AF groups, respectively. After adjusting for sex, age, previous anticoagulation, and initial National Institutes of Health Stroke Scale score, sustained AF was negatively associated with 3-month independence (multivariable-adjusted odds ratio, 0.61; 95% confidence interval, 0.43–0.87; P =0.006). The annual rate of stroke or systemic embolism was 8.3 and 4.6 per 100 person-years, respectively (multivariable-adjusted hazard ratio, 1.95; 95% confidence interval, 1.26–3.14) and that of major bleeding events was 3.4 and 3.1, respectively (hazard ratio, 1.13; 95% confidence interval, 0.63–2.08). Conclusions—: Among patients with previous ischemic stroke or transient ischemic attack, those with sustained AF had a higher risk of stroke or systemic embolism compared with those with paroxysmal AF. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01581502. Abstract : Supplemental Digital Content is available in the text.